The development of online checklist system for traffic impact assessment (e.C-TIA) report submission in Malaysia - Lim, Wei May (2020)
Rapid urbanisation and development lead to expansion of roads and accelerated land use demand causing congestion, accidents, pollution and other transportation-related problems. Traffic Impact Assessment is introduced and conducted to assess and mitigate traffic impacts generated from the proposed development and improve road safety. The reports provide the authorities, developers and consultants the framework in making critical land use and site planning decisions regarding traffic and transportation issues. However, the different reporting standard due to different level of knowledge and experience of stakeholders, institutionalisation of the practice as well as lack of cooperation cause fragmentation in the standard TIA report submission. Besides, there is no online system in Malaysia to assist the stakeholders. Hence, this research aims to develop an online checklist system as a standard platform to manage and monitor the TIA reports more effectively and efficiently. This developed system is verified by test case using information systems success model and validated using Delphi method for users’ satisfaction. This system enables consistency in fulfilling the requirements for TIA report based on guidelines by developers or consultants with standardised checklist and workflow and allows the authority who check multiple reports from different projects within 14 days. This research found that the system is useful as a managing tool for the coordination, collaboration and communication among stakeholders in reviewing, submitting, monitoring and updating the TIA report submission. Finally, the invited expert panel that evaluated the system was satisfied with the functionality of the design and flow of the system and 80% of them agreed that the system could be implemented in practice.